Compendium of organic synthetic methods : Volume 13 - Smith, Michael, 1946 October 17- (Hoboken, New Jersey : John Wiley & Sons, Inc., 2014)
The Compendium of Organic Synthetic Methods serves as a handy desktop reference for organic chemists to browse new reactions and transformations of interest, facilitating the search for functional group transformations in the original literature of organic chemistry. Volume 13 contains both functional group transformations and carbon-carbon bond forming reactions from the literature in the years 2005-8. It presents examples of published reactions for the preparation of monofunctional compounds. The Compendium of Organic Synthetic Methods series facilitates the search for q.
Section 39: alcohols and thiols from ethers, epoxides, and thioetherssection 40: alcohols and thiols from halides and sulfonates; section 41: alcohols and thiols from hydrides; section 42: alcohols and thiols from ketones; section 42a: reduction of ketones to alcohols; asymmetric reduction; non-asymmetric reduction; section 42b: alkylation of ketones, forming alcohols; asymmetric alkylation; non-asymmetric alkylation; section 43: alcohols and thiols from nitriles; section 44: alcohols and thiols from alkenes; section 45: alcohols and thiols from miscellaneous compounds.
Print version record.
Keywords: Organic compounds -- Synthesis; Acetylene compounds; Chemistry, Organic; Organic compounds -- Synthesis; Transition metals; SCIENCE -- Chemistry -- Organic; Organic compounds -- Synthesis; Electronic books